Pengembangan Buku Ajar Dengan Model Inkuiri Berbasis Strategi Konflik Kognitif Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Dahlia Rosma Indah; Husnul Hatimah (Universitas Pendidikan Mandalika Mataram, 2020)
Chemical bonding contains basic concepts that are used to understand almost any topic in chemistry. Several research results show that there are still many misconceptions. Therefore, teaching materials are needed that can provide a correct understanding of the basic concepts in chemical bonding materials. This study aims to produce inquiry model chemistry teaching materials with cognitive conflict strategies for Muallimat NW Pancor high school. The development method used definne, design, development and dissemination. Data analysis was conducted in the form of product validity tests and students' critical thinking skills tests. However, in this development research, it only stopped at the third stage. The data obtained were quantitative and qualitative. The results is (1) the feasibility of the material was 84% (very feasible); (2) the systematic feasibility of the presentation is 85% (very feasible); (3) language feasibility is 85.33% (very feasible). So that overall the teaching materials produced are categorized as very feasible and can be used in chemistry learning.